(untitled) (Journal of Asian Development Studies, 2019)
The study determines the impact of climate change and energy consumption on economic growth in Pakistan over the period from 1981 to 2014. With advanced energy appliances energy uses are increasing day by day and the use of this highly consumption rate taking implications on macroeconomic policies and structure. The study estimated ARDL approach of cointegration and UECM technique used to establish the long run and short run relationship among economic growth, CO2 emissions, energy consumption and the employment ratio. The results show that there are long run and short run relationships among the variables in the model. There is positive and significant impact of CO2 emissions, energy consumption, and employment ratio on per capita GDP in the long run. The results for direction of causality indicate that there is unidirectional relationship of carbon emissions per capita and energy consumption per capita on GDP per capita, but employment ratio causes GDP per capita in the short run. On the basis of our empirical findings, it can be concluded that energy conservation policies and controlling carbon dioxide emissions, are likely to have no adverse effect on economic growth in Pakistan in the short run.